A Teaching Experience of Two Courses About Modeling Methods and Object-Oriented Programming in an Undergraduate Program - Paz, Freddy; A. Paz, Freddy; Jesús Arenas, Juan (International Journal of Engineering and Technology, 2018)
The qualified use of advanced programming techniques for the development of enterprise software products, as well as, the proper application of modeling techniques in the design of software systems are two extremely relevant aspects in the curricula of an undergraduate software engineering student. In the Pontifical Catholic University of Peru (PUCP), these two important topics are taught by separated, in two different courses at the seventh semester of the Software Engineering career. The problematic situation with this curricular plan structure is that the students fail to relate concepts and theories whose usage is dependent one from the other. In a software development process, the analysis and design phases are key factors for the construction of a software that meets real needs of a certain group of users. However, when the computational programming and the modeling of software products are taught as independent concepts, the students tend to design only to complete the steps of the development process, and to write computer instructions without a vision and previous analysis of the system to be implemented. In this paper, we describe a teaching experience in which the authors employ collaborative strategies in a way that the students can figure out how the concepts are related and relevant for the construction and development of software products with high-quality standards.
Keywords: university teaching experience; educational case in software engineering; collaborative teaching; software development in an academic environment; a methodology for teaching in engineering.